Efforts to Handle Fish Waste as Animal Feed in Puday Village, Kendari City - Hajar; Harianti; Nurmaya; Hasriati; Tao, Harudin (PT FORMOSA CENDEKIA GLOBAL, 2024)
UNSULTRA Internal Community Service Activities (PKM-UNSULTRA) carried out by a team of lecturers from the Faculty of Agricultural Technology located at PPS Kendari City. Fish waste can be processed into animal feed, the result of which is simply processed into fish meal. Fish meal as an animal feed ingredient is made from processed residues (waste). Maximizing the use of fish waste will ultimately increase the economic value of the processed waste. Community service activities aim to process feed in the right way and apply it to livestock. Processing fish waste can maximize the economic value of feed. This is intended to be able to process fish waste properly, produce more and run a fishmeal business as animal feed in a more focused manner. The results of the activity show that there has been an increase in knowledge and skills in processing fish waste into better animal feed and there is practical packaging in marketing the product.